A century of air power the changing face of air warfare 1912-2012 - Sloggett, Dave (Pen & Sword Aviation, 2013)
No other technical development since the introduction of gunpowder has had as great an influence on warfare as the aircraft. In this wide-ranging and comprehensive study, David Sloggett investigates the changing role and increasing significance of air power over the course of the previous 100 years.